Patterns of population structure and complex haplotype sharing among field isolates of the green alga Chlamydomonas reinhardtii. Issue 17 (11th September 2019) - Craig, Rory J.; Böndel, Katharina B.; Arakawa, Kazuharu; Nakada, Takashi; Ito, Takuro; Bell, Graham; Colegrave, Nick; Keightley, Peter D.; Ness, Rob W.
Abstract: The nature of population structure in microbial eukaryotes has long been debated. Competing models have argued that microbial species are either ubiquitous, with high dispersal and low rates of speciation, or that for many species gene flow between populations is limited, resulting in evolutionary histories similar to those of macroorganisms. However, population genomic approaches have seldom been applied to this question. Here, we analyse whole‐genome resequencing data for all 36 confirmed field isolates of the green alga Chlamydomonas reinhardtii . At a continental scale, we report evidence for putative allopatric divergence, between both North American and Japanese isolates, and two highly differentiated lineages within N. America. Conversely, at a local scale within the most densely sampled lineage, we find little evidence for either spatial or temporal structure. Taken together with evidence for ongoing admixture between the two N. American lineages, this lack of structure supports a role for substantial dispersal in C. reinhardtii and implies that between‐lineage differentiation may be maintained by reproductive isolation and/or local adaptation. Our results therefore support a role for allopatric divergence in microbial eukaryotes, while also indicating that species may be ubiquitous at local scales. Despite the high genetic diversity observed within the most well‐sampled lineage, we find that pairs of isolates share on average ~9% of their genomes in long haplotypes, even when isolates were sampled decades apart and from different locations. This proportion is several orders of magnitude higher than the Wright–Fisher expectation, raising many further questions concerning the evolutionary genetics of C. reinhardtii and microbial eukaryotes generally. Abstract : See also the perspective by Sleith and Katz in the issue 28:22